Subcutaneous Cervical Emphysema After Labour Epidural Analgesia: - Rego, Sara Margarida (2019)
The authors report a rare case of iatrogenic subcutaneous cervical emphysema after lumbar epidural catheter insertion for labour analgesia. Although lumbar epidural analgesia is the gold standard in labour analgesia, some complications may occur. Subcutaneous emphysema is a rare complication following identification of the epidural space with loss-of-resistance technique with air. Being usually a self-limited condition, the treatment is conservative. Its resolution is dependent on the amount of air trapped and usually resolves in a few days. One way to avoid this complication is the use of saline solution in the loss of resistance technique for identification of the epidural space. If loss of resistance to the injection of air is to be used, it is necessary to adopt some preventive measures.